Braille and Tactile Graphics: Youths with Visual Impairments Share Their Experiences. (May 2015) - Rosenblum, L. Penny; Herzberg, Tina S.
Introduction: Data were collected from youths with visual impairment about their experiences with tactile graphics and braille materials used in mathematics and science classes. Methods: Youths answered questions and explored four tactile graphics made using different production methods. They located specific information on each graphic and shared their thoughts about the quality of the graphics. Results: Twelve youths in 6th to 12th grades participated. Almost all participants reported typically receiving braille materials and using tactile graphics in their mathematics and science classes. Participants varied in their accuracy in locating specific information in four tactile graphics. They all reported that what made a tactile graphic "good" was clarity of information. Discussion: The majority of the youths reported that occasionally they do not have access to mathematics and science materials at the same time as their peers. Some seemed concerned by the lack of materials, and others did not. The lack of materials may be problematic, since some of the students reported completing the assignments later or not at all. Youths overwhelmingly reported a need to have tactually distinctive elements in graphics. Implications for practitioners: Professionals should consult youths when preparing materials for them for use in mathematics and science classes. Additionally, youths who are tactile readers need direct instruction in how to measure objects as well as how to locate specific information in a variety of graphics prepared using different production methods.